(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
To study the motion law of low-speed ceramic ball penetrating gelatin,the impact velocity and penetration gelatin depth of ceramic ball with different diameters were measured by experiment and numerical simulation. The penetration depth of spherical fragments into gelatin was calculated by using the energy conservation model. The experimental results and theoretical results were combined to verify the calculation. The results show that the penetration depth calculated by the theoretical analysis model in this paper is in good agreement with the experimental results. Based on the reliability of the theoretical model,it was found that the diameter of low-speed ceramic ball penetrating gelatin was the main factor affecting the penetration depth. By comparing the penetration ability of ceramic ball,tungsten ball and steel ball were compared,and the penetration depth and cavity radius were considered. The results show that ceramic ball is more suitable to be used as damage element.